АЛГОРИТМЫ И ПРОГРАММНОЕ ОБЕСПЕЧЕНИЕ ДЛЯ АВТОМАТИЧЕСКОГО РЕДАКТИРОВАНИЯ ОРФОГРАФИИ УЗБЕКСКИХ СЛОВ - Эшкараева, Н.Г.; Боймуродов, Ф.Ф. (SCIENCE and SOCIETY, 2025)
The article discusses the UZMORF program and tools written in the Python programming language for natural language processing (NLP), which is one of the main areas of computational linguistics. This program was created to automate the editing and processing of Uzbek words, their spelling and grammar. The system works with texts and performs syntactic and morphological analysis of words. As a result of these analyses, the system identifies words and their grammatical solutions and marks places where there are errors.
Keywords: NLP; spelling correction; grammatical correction; uzmorf